Nutrition antioxidant status and oxidative stress in professional basketball players: effects of a three compound antioxidative supplement - Schröder, H.; Navarro, E.; Tramullas, A.; Mora, J.; Galiano, D. (International Journal of Sports Medicine, 2000)
Professional basketball players of the First Spanish League (ACB) are highly trained athletes performing high training loads and competition sessions. As intense physical activity has been suggested to increase free radical production, we examined the effects of a vitamin antioxidant mixture on the degree of oxidative stress in these athletes. Subjects received either 600 mg alpha-tocopherol, 1,000 mg vitamin C and 32 mg beta-carotene, or a placebo over 32 days during a regular competition season. Plasma concentrations of alpha-tocopherol, vitamin C, beta-carotene, retinol, lipoperoxides (LPO), and the total antioxidant status (TAS) were analysed before and after treatment. Lipoperoxide plasma levels decreased significantly (p < 0.05) in the vitamin antioxidant supplemented group. The LPO/TAS ratio decreased about 15.3% in this group indicating a reduction in oxidative stress. Vitamin C dropped dramatically (p < 0.03, mean 15.4 micromol/L) in the placebo group leading to a marginal plasma vitamin C concentration (from 11 to less than 28 micromol/L). The results of this study suggest that the administered vitamin antioxidant mixture decreases oxidative stress and avoids the development of a marginal vitamin C status in professional basketball player during habitual training.